Kindergarten Teachers' Perception of Outbound Activities in influencing multiple intelligence of early childhood - Muhammad Andri Setiadi; Mubiar Agustin (IKIP Siliwangi, 2020)
The main occupation in childhood is playing. Therefore, education in early childhood is done with a variety of fun games. Outbound activities are one alternative learning activities for early childhood. This activity consists of various games that are fun and have benefits in early childhood development. Teachers as instructors must have knowledge related to the right games in outbound activities to be appropriate in helping the child's growth and development. This study aims to reveal the kindergarten teacher's perception of outbound activities in influencing the complex intelligence of early childhood in the form of linguistic intelligence, mathematics, music, visual-spatial, naturalist, interpersonal, and intrapersonal. This research is a survey research with quantitative approach. The population and sample in this study were kindergarten and PAUD teachers in Greater Bandung. The sample technique used is snowball sampling. The questionnaire used to obtain data was arranged using a Likert scale. Research data were analyzed using proportion analysis and mode analysis. The results showed the interpretation of teachers' perceptions of outbound activities in influencing compound intelligence of early childhood is positive.Pekerjaan utama pada masa kanak-kanak adalah bermain. Oleh karena itu pendidikan anak usia dini dilakukan dengan berbagai permainan yang menyenangkan. Kegiatan outbond adalah salah satu laternative kegiatan pembelajaran untuk anak usia dini. Kegiatan ini terdiri dari berbagai permainan yang menyenagkan serta memiliki manfaat dalam perkembangan anak usia dini. Guru sebagai pengajar harus memiliki pengetahuan terkait permainan yang tepat dalam kegiatan outbond agar sesuai dalam membantu tumbuh kembang anak.Penelitian ini bertujuan untuk mengungkapkan persepsi guru taman kanak-kanak terhadap kegiatan outbond dalam mempengaruhi kecerdasan majemuk anak usia dini berupa kecerdasan linguistik, matematika, music, visual-spasial, naturalis, interpersonal, serta intrapersonal. Penelitian ini merupakan penelitian survey dengan pendekatan kuantitatif. Populasi dan sampel dalam penelitian ini adalah guru taman kanak-kanak dan PAUD di Bandung Raya. Teknik sample yang digunakan adalah snowball sampling. Angket yang digunakan untuk memperoleh data di susun menggunakan skala likert. Data penelitian di analisis menggunakan analisis proporsi dan analisis mode. Hasil penelitian menunjukan interpretasi persepsi guru terhadap kegiatan outbond dalam mempengaruhi kecerdasan majemuk anak usia dini bernilai positif.